Top dog [large type] : the story of marine hero Lucca - Goodavage, Maria, 1962- (Center Point Large Print, 2015)
"The story of Marine K9 hero Lucca and the handlers who fought alongside her through two bloody wars in Iraq and Afghanistan"--